2015
DOI: 10.1021/acs.organomet.5b00087
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of the Mechanisms of Iron-Catalyzed Intramolecular C–H Amination [1,2]-Shift Tandem Reactions of Aryl Azides

Abstract: The mechanisms of iron­(II) bromide-catalyzed intramolecular C–H bond amination [1,2]-shift tandem reactions of aryl azides have been studied using density functional theory calculations. The tandem reaction from R 1 , 1-azido-2-(1-methoxy-2-methylpropan-2-yl)­benzene, to produce P 2 , 2,3-dimethyl-1H-indole, was calculated. Our results showed that the overall catalytic cycle includes the following steps: (I) extrusion of N2 to form iron nitrene; (II) C–H bond amination; (III) formation of the middle product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The observation on the retention of the cyclopropyl group, on the other hand, suggests that the C-H bond amination step in this FeBr 2 -catalzyed reactions might be distinct from the classical H-abstraction/radical rebound mechanism. Ren and coworkers performed DFT calculations on the mechanism of this FeBr 2 -catalzyed reaction, [71] and found that a concerted *2σ+2π+-addition between iron imido moiety and a C-H bond to form iron amido hydrido species is energetically favored over the classical radical type C-H amination mechanism (Scheme 10).…”
Section: C-h Bond Amination Reactions Catalyzed By Non-heme-type Ironmentioning
confidence: 99%
“…The observation on the retention of the cyclopropyl group, on the other hand, suggests that the C-H bond amination step in this FeBr 2 -catalzyed reactions might be distinct from the classical H-abstraction/radical rebound mechanism. Ren and coworkers performed DFT calculations on the mechanism of this FeBr 2 -catalzyed reaction, [71] and found that a concerted *2σ+2π+-addition between iron imido moiety and a C-H bond to form iron amido hydrido species is energetically favored over the classical radical type C-H amination mechanism (Scheme 10).…”
Section: C-h Bond Amination Reactions Catalyzed By Non-heme-type Ironmentioning
confidence: 99%
“…The hydroxylation of unactivated methylene catalyzed by P450 PikC that is engineered from pikromycin natural biosynthetic pathway has been examined . However, computational studies on P450 with an iron nitrenoid cofactor that can functionalize C–H bonds are lacking, although there were studies on iron nitrenoid-mediated C–H activations without P450. In this work, the mechanism of P450-catalyzed C–H amination was studied by QM/MM calculations. On the basis of this study, the regio- and stereoselectivity of this reaction can be explained.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Bredt’s rule, the intermediate V with a bridgehead double bond is highly strained and thus will go through rearrangement quickly. Through a multistep rearrangement, , the intermediate V transformed to the final product 3 .…”
mentioning
confidence: 99%
“…6 No formation of their corresponding cyclopenta [c] will go through rearrangement quickly. Through a multistep rearrangement, 11,12 the intermediate V transformed to the final product 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation